THE P-Δ-DUCTILITY EFFECT : OVERVIEW THE EFFECT OF THE SECOND ORDER IN THE DUCTIL STRUCTURES - Rafael Shehu (European Scientific Journal, ESJ, 2014)
Building behavior is a function of a number of factors and their interactions versus external action chosen by us. This discussion rises above the geometry of the structure, its hardness and their connections functions. The main parameters of the connections functions are loads and the calculation stage. With loads we mean static and dynamic ones, while the calculation stage I refer to the phase behavior of the material and structure, the elastic stage or post elastic stage , without deformed or deformed elements. Each stage is realized or lets say , approximate in calculations methods and modifying some standard procedures. In this discussion we will address in a concise way , two key factors in the design of structures, which are second order effects (P-Δ) and the ductility of structures. Both factors have emerged as a necessity of approximating real complex behavior in a calculation methodology. Will hope to better understand the interaction of these two design factors, studying different methodology and approach to the problem by comparing the design requirements. What we stand for discussions , is to increase the accuracy of structural analysis for structures at the design stage of internal forces. It is known that a nonlinear analysis is more accurate than a linear analysis, but on the other hand is an inefficient analysis in terms of time consuming with calculations and computer memory. The solution in our case would require a small memory and fast time.